Os efeitos socioespaciais da expansão canavieira na bacia hidrográfica do rio Ivinhema no Estado de Mato Grosso do Sul - Teixeira, Jodenir Calixto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this paper, the results are presented of the investigation held in the hydrographic basin area of the Ivinhema river, in the State of Mato Grosso do Sul, which had the objective of analyzing the sugarcane expansion in this space, in the past twelve years, and its effects on the aforementioned space. Besides the bibliographic research, data from secondary sources was raised, interviews held with key people and forms applied to rural producers distributed in 24 of the 25 municipalities that integrate the hydrographic basin of the Ivinhema River. The hydrographic basin area studied presented strong expansion of the sugar alcohol activity in the past years, above all in the 2000s, when several sugar and alcohol mills were installed and sugarcane fields began to cover extensive areas. The sugarcane culture expansion took place, especially, in areas previously occupied by pastures and, in smaller proportion, in spaces that were occupied by other large plantations, especially soy and corn. At the end of the 2000s, the sugar alcohol industry went into crisis and currently there is a decrease in the sugar cane cultivation areas and greater expansion of soy culture, however, the pasture areas continue in a retraction process...

No presente trabalho são apresentados os resultados da investigação realizada na área da bacia hidrográfica do rio Ivinhema, no Estado de Mato Grosso do Sul, cujo objetivo foi analisar a expansão canavieira nesse espaço, nos últimos doze anos, e seus efeitos sobre o referido espaço. Além de pesquisa bibliográfica, foi efetuado levantamento de dados de fontes secundárias, realizadas entrevistas com pessoas chaves e aplicados formulários a produtores rurais distribuídos em 24 dos 25 municípios que integram a bacia hidrográfica do rio Ivinhema. A área da bacia hidrográfica estudada apresentou forte expansão da atividade sucroalcooleira nos últimos anos, sobretudo na década de 2000, quando foram instaladas várias usinas de açúcar e álcool e os canaviais passaram a ocupar vastas extensões. A expansão da cultura canavieira ocorreu, principalmente, sobre áreas anteriormente ocupadas por pastagens e, em menor proporção, em espaços que eram ocupados por outras grandes lavouras, principalmente soja e milho. No final da década de 2000 o setor sucroalcooleiro entrou em crise e na atualidade está havendo a diminuição das áreas de cultivo de cana-de-açúcar e maior expansão da sojicultura, no entanto, as áreas de pastagens continuam em processo de retração...
Keywords: Geografia; Cana-de-açúcar - Cultivo - Mato Grosso do Sul; Agroindústria - Mato Grosso do Sul; Agropecuaria - Mato Grosso do Sul; Desenvolvimento rural - Mato Grosso do Sul; Lavoura - Mato Grosso do Sul; Geography